Stylistic Analysis in a Collection of Poetry Tears of Batu by Fakhrunnas Ma Jabbar - Suci Eliani; Sudirman Shomary (UIR Press, 2022)
Literature is a work of art that produces beautiful creative works that can be poured or created by humans. The beauty of language is easily seen in literary works, especially by using stylistic analysis. Therefore, the author is interested in conducting a research entitled